Addis deals: reckoning with the informal governance of urban structural transformation - Selam Robi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
African cities are increasingly seen as key to unlocking national structural transformation and inclusive growth, as they tend to host the majority of the non-productive and informal labour force; attract the lion's share of domestic investment in non-productive sectors; and host different political-economic relations and power configurations to those observed at the national scale. While a growing body of literature is therefore calling for the study of structural transformation at the city level in Africa, this scholarship has neglected the political economy and, more importantly, the informal governance of urban structural transformation. Building on the Deals and Development framework's approach to the problem of inclusive growth and structural transformation in fragile states, this research interrogates the implications of urban political settlements for the prospects of urban structural transformation in a rapidly growing African city, Addis Ababa. Through the thematic analysis of qualitative interviews with key actors in the domain of structural transformation in Addis Ababa, I investigate the evolution of the city's deals spaces following the recent regime change in Ethiopia. I find that the emerging political settlement has further closed and disordered deals spaces for the city's workhorse and magician firms, inhibiting their survival, growth, and productivity, while opening up new deals spaces and expanding rents for the city's power brokers. The paper concludes that the nature of the evolution of Addis Ababa's deals spaces has negative implications not only for structural transformation at city and national scales but also for the stability and longevity of the current national political unsettlement. The paper advances debates on the role of informal economic governance in African cities for city- and national-level economic growth, structural transformation, and political order.
Keywords: L14; L16; 330; urban structural transformation; informal economic governance; urban political settlements; deals spaces; African cities